2020
DOI: 10.20396/bjos.v19i0.8661025
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sleep bruxism in children in primary dentition

Abstract: Aim: To evaluate the prevalence of sleep bruxism in childrenbetween 2 to 6 years old in primary dentition in a public school(A1) and a private school (A2) in the state of Piauí. Method: Itwas cross-sectional and quantitative study in 370 participants,180 in A1 and 190 in A2. The questionnaire to help diagnosebruxism was applied to parents. In the clinical examination,dental wear was evaluated, checking for the presence ofshiny and polished facets on deciduous incisors and / ormolars (palatal surface, incisal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Some studies showed an association between sleep bruxism [ 46 ] and the habits of finger sucking, the use of pacifiers and/or bottles. Present results support this notion (children who used a pacifier and or sucked their finger showed a higher prevalence of SB than children who did not perform these habits).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed an association between sleep bruxism [ 46 ] and the habits of finger sucking, the use of pacifiers and/or bottles. Present results support this notion (children who used a pacifier and or sucked their finger showed a higher prevalence of SB than children who did not perform these habits).…”
Section: Discussionmentioning
confidence: 99%